IMPLEMENTASI MODEL PEMBELAJARAN SENTRA DALAM PENGEMBANGAN NILAI AGAMA DAN MORAL ANAK - R, Nurhasanah; Wardan, Yulvina; Dwiyama, Fajri (EDUCHILD (Journal of Early Childhood Education), 2022)
This study discusses developing children's religious and moral values through learning centers at TK IT Asshiddiq Kabupaten Bone. The purpose of this study was to describe the development of children's religious and moral values through learning center models, knowing the center learning models and efforts to develop children's religious and moral values. To obtain data in this study, researchers used qualitative research methods, with descriptive analysis. Data collection techniques used in this study were observation, interviews and documentation. Based on the results of the research conducted, it was concluded that learning center models were able to develop children's religious and moral values. The centers that are able to develop children's religious and moral values in TK IT Asshiddiq Kabupaten Bone Regency are preparation centers, blocks centers, roleplaying centers, natural materials centers and art centers besides the centers there are also habituation activities and methods methods to further optimize the development of children's religious and moral values.